2021
DOI: 10.1038/s41394-021-00408-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of traumatic spinal cord injuries in Colombia

Abstract: Study Design: Retrospective cohort study. Objectives: To determine the incidence and characteristics of newly injured individuals admitted to a traumatic spinal cord injury (TSCI) referral center during a 4-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Our findings and previous reports showed that the majority of TSCI result from falls on level ground in Japan [ 11 , 12 ], while low- to middle-income countries experience a particularly high frequency of TSCI caused by violence. An epidemiological study in Colombia revealed that interpersonal violence is the most common mechanism of TSCI in the region [ 38 ]. Notably, the severity of TSCI resulting from interpersonal violence often leads to a high percentage of ASIA grade A (complete paralysis).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings and previous reports showed that the majority of TSCI result from falls on level ground in Japan [ 11 , 12 ], while low- to middle-income countries experience a particularly high frequency of TSCI caused by violence. An epidemiological study in Colombia revealed that interpersonal violence is the most common mechanism of TSCI in the region [ 38 ]. Notably, the severity of TSCI resulting from interpersonal violence often leads to a high percentage of ASIA grade A (complete paralysis).…”
Section: Discussionmentioning
confidence: 99%
“…In an international study the most frequent injury patterns were incomplete paraplegia with 34.5% of the studied population and incomplete paraplegia with 28.1% (3). In Colombia, according to studies in the 1990s and 2000s, the population with spinal cord injury was younger, with an average age of 32 years, men represented 85% of the population, injuries were more frequent at the thoracic level and the main etiology was violence with 40% of the cases, especially rearm injuries (4,5).…”
Section: Introductionmentioning
confidence: 95%
“…The manuscripts tackled topics in the fields of hematology and oncology, [17][18][19][20][21][22][23] ethics (e.g., diversity, equity and inclusion), [24][25][26][27] infectious diseases, 28,29 surgery, 30,31 pediatrics, 32 and physical and rehabilitation medicine. [33][34][35] We invite you to read them and encourage you to include students and early career scientists in your research projects.…”
Section: How To Make Editors and Scientists: An Ijms Initiativementioning
confidence: 99%